Pengaruh Tingkat Kepercayaan, Persepsi Tax Amnesty, Akuntabilitas Pelayanan Publik, dan Lingkungan Sosial terhadap Kepatuhan Wajib Pajak Orang Pribadi - Dewi, Ni Putu Desi Arya; Diatmika, I Putu Gede (Universitas Pendidikan Ganesha, 2020)
The purpose of this study is to determine the effect of the level of trust, perceptions of tax amnesty, accountability of public services, and social environment on the compliance of individual taxpayers who are registered in KPP Pratama Tabanan-Bali. The quantitative method was chosen to be the method of this study using primary data in the form of questionnaire. Based on the data obtained there are 56,574 Individual Taxpayers who have NPWP and have also entered the SPT mandatory list at the Tabanan-Bali Primary Tax Office in 2019. Data collected through a questionnaire that is distributed online using google form as a form of covid prevention 19. Multiple linear regression methods with SPSS version 25 for Windows program help are used in analyzing the data obtained. From this study, found a positive and significant influence given by the level of trust in the compliance of the Individual Taxpayer. Perception of tax amnesty also has a positive and significant effect on the compliance of the mandatory taxpayers of individuals. Furthermore, personal tax compliance1 is influenced positively and significantly and compliance. Personal taxpayers are influenced positively and significantly by the social environment.